DEVELOPMENT OF ANALYSIS STUDY ON MAINTENANCE DOWNTIME (MAINTAINABILITY) OF EQUIPMENT AND SYSTEM IN PETROCHEMICAL PLANT - AHMAD KAMAL, UMAR MUSLIM (IRC, 2021)
Maintenance Downtime is a process when a system or equipment is not running or productive due to maintenance work needed.